A Mixed‐Methods Study: Sex Differences in Experiences of Stigma Associated With Alcoholism and Alcohol Use Disorders Among Injury Patients in Tanzania. (9th August 2020) - Griffin, S. Michelle; Karia, Francis P.; Zimmerman, Armand; Minnig, Mary Catherine C.; Swahn, Monica; Makelarski, Jennifer; T. Mmbaga, Blandina; Vissoci, João Ricardo Nickenig; A. Staton, Catherine
Abstract : Background: Each year, alcohol use causes 3.3 million deaths globally and accounts for nearly 30% of injuries treated at Kilimanjaro Christian Medical Center (KCMC) in Moshi, Tanzania. Prior research found significant stigma toward patients reporting alcohol use in general and among healthcare providers for this population. Methods: This mixed‐methods study aimed to identify sex‐based perspectives of stigma among injury patients, family members, and local community advisory board (CAB) members. Injury patients from the emergency room at KCMC were asked to complete surveys capturing consumption of alcohol, perceived stigma, and consequences of drinking. Patients who completed the survey, their family members, and members of a CAB were also recruited to take part in focus groups led by a trained bilingual research nurse. Data were analyzed using multiple linear regression and Wilcoxon rank sum tests with alpha level set at 0.05. Results: Results showed that sex was a significant predictor of perceived discrimination ( p  = 0.037, Standard Error (SE) = 1.71 (0.81)) but not for perceived devaluation ( p  = 0.667, SE = −0.38 (0.89)). Focus groups revealed there were global negative perceptions of the amount of alcohol consumed as well as negative perceptions toward disclosure of alcohol use to healthcare providers. Sex differences in stigma emerged when participants were specifically asked about women and their alcohol consumption. Conclusions: The findings of this study suggest there is an underlying sex difference, further stigmatizing women for alcohol use among the injury patient population at KCMC. Tanzanian women suffer from unequal access to health care, and the stigmatization of alcohol use likely increases this disparity.